The Peripheral Serotonergic System and Platelet Aggregation in Cyclosporin A-Induced Hypertensive Rats - Reis, Flávio (1999)
Cyclosporin A plays an important role in preventing rejection in allograft transplant recipients. However, the therapeutic use of cyclosporin A is associated with increased incidence of thromboembolic complications and drug-related hypertension. In order to study the mechanisms by which cyclosporin A induces these abnormal pathophysiological situations, we have assessed the platelet serotonin contents and whole blood platelet aggregation in control rats as well as in rats treated (orally) with 30 and 5 mg/kg/day of cyclosporin A, after 2 and 7 weeks of treatment. These doses correspond respectively to CsA "peak" and "trough" concentrations achieved in human blood in clinical practice (immediately following an intake of a daily dose of CsA and when the blood concentration stabilizes, respectively). Both trough and peak doses caused an increase in blood pressure after 2 and 7 weeks. Platelet serotonin content decreased in the cyclosporin-treated groups, in contrast with the control. Collagen-induced whole blood platelet aggregation increased drastically for the peak concentration-treated group, while adenosine 5'-diphosphate-induced platelet aggregation did not reach statistical significance. Finally, in vitro platelet thromboxane A2 generation increased in cyclosporin A concentrations when platelets were stimulated with either collagen or adenosine 5'-diphosphate. In conclusion, both tested cyclosporin A concentrations induced important changes in platelet serotonin and thromboxane content and aggregation, factors which may play a decisive role in the development and/or maintenance of hypertension and thrombotic complications.